[PP.05.01] EFFECT OF LONG-TERM ENRICHED POTASSIUM SALT INTAKE ON SALT REDUCTION IN CHINESE LIVING IN NURSING HOUSES. (September 2017) - Wang, X.; Li, W.; Li, D.; Guo, Y.; Zhang, B.; Zhao, J.; Dong, Y.; Liu, Y.; Dou, X.; Zhang, H.; Liu, L.
Abstract : Objective: To explore whether long-term enriched potassium salt intake (KCL/NACL = 1:1 by weight) can achieve the purpose of salt reduction in Chinese living in nursing houses. Design and method: Participants were recruited from 28 nursing houses in 4 Northern provinces and Beijing City in 2012. The nursing houses were then randomized into 2 groups: normal salt (control group) and enriched potassium salt (intervention group), Health education about the benefits of salt restriction were provided for all participants. The follow-up visits including questionnaire and spot urine collection were carried out in 24–31 month and 48 month. The contents of questionnaire included the consumption of various high salt materials and number of dinners in the last month, the average salt intake per person per day at baseline and follow-up visits were calculated according to food composition table. The results of spot urine electrolytes and the salt consumption at baseline and follow-ups were used for data analysis. Results: Totally 2779 participants (intervention group 1336, control group 1443) were included in this study. The average salt intake per person per day for intervention group and control group at baseline were 12.86 ± 4.80 g and 12.58 ± 2.85 g respectively p = 0.85. No difference were found between average salt intake of two follow-up visits of control group with that at baseline (p = 0.69 and p = 0.59). But, the salt consumption were decreased in intervention group to 6.89 ± 1.78 g (24–31 month follow-up), 8.75 ± 3.34 g (48 month-follow-up), p < 0.001 compared with baseline. Urinary sodium potassium ratio (UNA/K) between control and intervention groups at baseline were 7.86 vs. 8.22, p = 0.12. While, at 48th month follow-up, the UNA/K of intervention group was significantly lower than control group 2.46 ± 1.71 vs. 4.21 ± 2.27, p < 0.001. Conclusions: Our study demonstrated that long-term enriched potassium salt intake can reduce dietary salt consumption and urine sodium potassium ratio. It might be an effective way for dietary salt restriction. Present data were from the cafeteria staff self-report and spot urine, further verification by 24 hours urine specimens were necessary.